Relationship Between Scene and Sountrack of Teenager’s Frustration and Anger Reflected on The End of The F***ing World Series (2017) - Ahmad Aufarul Lutfi; Atinia Hidayah (Metaphor, 2022)
This study is aimed to analyze: (1) The scenes in The End of the F***ing World Series (2017) that depict teenagers’ frustration and anger. The study uses a qualitative method to analyze the film entitled “The End of the F***ing World” as the objective research. The researcher analyzes the data by using semiotics and takes some steps of watching, reading the subtitle, identifying, classifying, and selecting data. Afterward, the step is continued by analyzing data through the process of displaying, explaining, and interpreting the data The result shows that the scenes portrayed teenagers’ frustration and anger caused by their personal, family, and social problems.